Exposure assessment of epoxy fatty acids through consumption of specific foods available in Belgium - Mubiru, Edward; Jacxsens, Liesbeth; Papastergiadis, Antonios; Lachat, Carl; Shrestha, Kshitij; Mozumder, N. H. M. Rubel; De Meulenaer, Bruno (Food Additives & Contaminants, 2017)
Epoxy fatty acids (EFAs) are secondary oxidation products formed from unsaturated fatty acid hydroperoxides. Seventeen food categories were analysed for C18 monoEFAs of food products available on the Belgian market. A quantitative exposure assessment was performed based on deterministic and probabilistic approaches combining these concentration data with consump- tion data obtained from the Belgian National Food Consumption Survey of 2004. A preliminary evaluation of any potential risk related to the intake of the studied EFAs through the studied foods was performed by applying the threshold of toxicological concern (TTC) concept. Three food categories out of 17 foods, mayonnaise, butter–margarine and ready-to-eat meals were found to contribute most to the intake of EFAs. According to probabilistic determination, these foods had P50 intakes of 0.4085, 0.3328 and 0.2997 mg kg–1 bw day–1 respectively. They had P99.5 intakes of 3.7183, 2.7921 and 38.6068 mg kg–1 bw day–1 respectively. The intake below the TTC was from the consumption of cooked meat, smoked salmon and raw cured ham, with P50 intakes of 0.0006, 0.0007 and 0.0011 mg kg–1 bw day–1 respectively, and the other foods were above the TTC. Based on the TTC concept, a risk to human health could be identified related to the consumption of cheese, snacks foods, plant oils, French fries, dry nuts, chips, cured minced raw meat, cookies, fresh and frozen salmon and bacon.
Keywords: Lipid oxidation; Fatty acid methyl esters; Threshold of toxicological concern; Risk assessment; Exposure assessment